A lanolina anidra combinada à educação em saúde no pré-natal para prevenção da dor e trauma mamilar em lactantes: ensaio clínico randomizado - Oliveira, Flávia Silva e (2019)
INTRODUCTION: Nipple pain and trauma are multifactorial breast complications with higher incidence at the beginning of breastfeeding. They are considered predictive factors for early weaning. There is still not enough evidence in the literature to recommend a method as the best in preventing nipple pain and trauma. OBJECTIVE: To compare the effect of anhydrous lanolin combined with health education on prevention of nipple pain and trauma with health education on breastfeeding in lactating women. METHODOLOGY: A randomized, controlled, open clinical trial with 82 women undergoing prenatal care in the public health care system, with a gestational age of 35 weeks or more. Data collection took place between May 2018 and February 2019. Women were randomized using computer-generated numbers (1: 1) in control group (41) and experimental group (41). In the experimental group, the women received the anhydrous lanolin ointment for immediate use, health education through an illustrated serial album and didactic breast demonstration; in the control group, the women were oriented according to the breastfeeding health education protocol. Women were evaluated on the 8th postpartum day for the occurrence of pain in the nipple and areola region determined by numerical pain scale, nipple trauma verified by clinical breast examination and breastfeeding technique observed by the breastfeeding assessment form. RESULTS: There was no significant difference between the groups. Pain affected 60.6% of women, of these 60.0% reported pain in both nipples, with predominant onset on the second postpartum day (p = 0.614). For the experimental group there was pain of low intensity, and for the control group moderate intensity (p = 0.276). Less than half of women (40.9%) had nipple trauma (p = 0.211), of these 74.0% had bilateral nipple trauma, beginning on the second postpartum day (p = 0.127). Lanolin associated with breastfeeding health education increases the prevention of nipple pain (RAR 6.1; NTT 21) by 6% and the prevention of nipple trauma (RAR 15.2%; NTT 6) by 15%. In breastfeeding evaluation, all parameters favorable to breastfeeding were observed, except for the condition of the breasts (p = 0.215). CONCLUSION: Anhydrous lanolin combined with health education has positive effects on the prevention of pain and nipple trauma; however, it was not significantly superior to health education on breastfeeding alone.